2019
DOI: 10.1016/j.amepre.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Dependence and Pre-Enlistment Suicidal Behavior Among U.S. Army Soldiers

Abstract: Introduction: Identification of modifiable risk factors for suicidal behaviors is a priority for the U.S. Army. This study investigated associations of nicotine dependence with suicidal behaviors among incoming soldiers.Methods: Lifetime DSM-IV nicotine dependence, mental disorders, suicidal behaviors, and their ages of onset were retrospectively assessed in the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS) New Soldier Study. Discrete-time survival analysis of personyear data from 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Similarly, Naifeh et al reported substance use associated with an increased risk of SA, 25 and Campbell-Sills et al noted associations between nicotine dependence and increased odds of SI and SA among a sample of Army soldiers. 26 We found consistent evidence that the number of cigarettes/day for the past 30 days and number of e-cigarettes for the past 30 days were both significantly associated with SI and SA, indicating the odds increasing by 0.3% for every additional cigarette or e-cigarette used. Mental health counselors or psychiatrists 4612 might consider screening for the level of tobacco dependence of an adolescent, and adolescent should, therefore, be carefully assessed as part of the psychiatric evaluation and management.…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, Naifeh et al reported substance use associated with an increased risk of SA, 25 and Campbell-Sills et al noted associations between nicotine dependence and increased odds of SI and SA among a sample of Army soldiers. 26 We found consistent evidence that the number of cigarettes/day for the past 30 days and number of e-cigarettes for the past 30 days were both significantly associated with SI and SA, indicating the odds increasing by 0.3% for every additional cigarette or e-cigarette used. Mental health counselors or psychiatrists 4612 might consider screening for the level of tobacco dependence of an adolescent, and adolescent should, therefore, be carefully assessed as part of the psychiatric evaluation and management.…”
Section: Discussionsupporting
confidence: 72%
“…There are known modifiable targets for suicide such as smoking [25][26][27][28], lipid and cholesterol profiles [29][30][31], dietary patterns [32], unemployment [33] and BMI in which overweight and obese individuals had lower suicide risk [34,35]. Likewise, a meta-analysis reported that compared to those with normal weight, underweight people had higher suicide risk and overweight people had lower suicide risk [36].…”
Section: Introductionmentioning
confidence: 99%